Factors Determining the Customers' Intention to Purchase OTC Products through E-Pharmacies - R., Krishnadas; R., Renganathan (INTI International University, 2022)
In the health care system, over-the-counter (non-prescribed) drugs play a crucial role in the medication process. Over-the-counter (OTC) drugs are medicinal products sold without a doctor's prescription. Without seeking care from health professionals, OTC medications are safe and effective for the general public usage. Generally, OTCs and self-medicines are used to treat mild health issues in a simpler and inexpensive way. Cold-and-cough medicines, vitamins, analgesics, digestive medicine (i.e., anti-acids), and dermatological medicines are the categories that dominate the world's top five OTC market-share. Limited studies in India aimed at evaluating OTC purchasing behaviour in e-pharmacies. Therefore, this study aimed to identify influential E-pharmacy factors that are affecting consumers during OTC products purchase. This study also examined the consumers' intention to purchase OTC products across major cities of Tamil Nadu. A total of 153 responses were collected from e-pharmacy customers through self-administered questionnaires across 4 major cities of Tamil Nadu. E-pharmacy customers who made at least one purchase on the e-pharmacy website were considered for the study. Based on the results, analgesic drugs are the most preferred OTC category in the online purchase mode. The results also demonstrated that post-purchase behaviour aspects like on-time delivery of the product and providing the shift response to solve the queries raised by the e-pharmacy customers play a significant role in enhancing customer satisfaction across e-pharmacy sites.